Recent advances in the role of sphingosine 1‐phosphate in cancer. Issue 22 (4th October 2020) - Pyne, Nigel J.; Pyne, Susan
Abstract : Sphingosine 1‐phosphate (S1P) is a bioactive lipid that binds to a family of G protein‐coupled receptors (S1P1–5 ) and intracellular targets, such as HDAC1/2, that are functional in normal and pathophysiologic cell biology. There is a significant role for sphingosine 1‐phosphate in cancer underpinning the so‐called hallmarks, such as transformation and replicative immortality. In this review, we survey the most recent developments concerning the role of sphingosine 1‐phosphate receptors, sphingosine kinase and S1P lyase in cancer and the prognostic indications of these receptors and enzymes in terms of disease‐specific survival and recurrence. We also provide evidence for identification of new therapeutic approaches targeting sphingosine 1‐phosphate to prevent neovascularisation, to revert aggressive and drug‐resistant cancers to more amenable forms sensitive to chemotherapy, and to induce cytotoxicity in cancer cells. Finally, we briefly describe current advances in the development of isoform‐specific inhibitors of sphingosine kinases for potential use in the treatment of various cancers, where these enzymes have a predominant role. This review will therefore highlight sphingosine 1‐phosphate signalling as a promising translational target for precision medicine in stratified cancer patients. Abstract :